2005
DOI: 10.1111/j.1439-0507.2004.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Candida species isolated from urine at an intensive care unit

Abstract: Candida spp. has been the leading microorganism isolated from the urine specimens of patients hospitalized at the Anesthesiology and Reanimation intensive care unit (ICU) of Dokuz Eylul University Hospital, Izmir, since 1998. This study was undertaken to investigate the clonal relationship of Candida urine isolates in order to find the mode of spread among the patients. Epidemiological surveillance of 38 Candida albicans, 15 Candida tropicalis and 12 Candida glabrata recovered from the urine specimens of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
2
14
0
1
Order By: Relevance
“…The reasons for the rising incidence of C. parapsilosis candidemia are not completely known, although indwelling venous catheters and parenteral nutrition have been recognized as specific risk factors [4,17,18]. Most experimental studies have indicated that the adherence of C. parapsilosis to acrylic surfaces is greater than that of C. albicans [19].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the rising incidence of C. parapsilosis candidemia are not completely known, although indwelling venous catheters and parenteral nutrition have been recognized as specific risk factors [4,17,18]. Most experimental studies have indicated that the adherence of C. parapsilosis to acrylic surfaces is greater than that of C. albicans [19].…”
Section: Discussionmentioning
confidence: 99%
“…The investigation performed by Szweda et al (2013) revealed 26 genotypes among 54 C. glabrata isolates, but it is noteworthy that the authors used only one primer in the study. Additionally, Ergon and Gülay (2005) observed a lower degree of genetic diversity among C. glabrata strains. The authors suggested that it is possible that primers used in the study were not appropriate for the typing of non-albicans species (Ergon & Gülay 2005).…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, Ergon and Gülay (2005) observed a lower degree of genetic diversity among C. glabrata strains. The authors suggested that it is possible that primers used in the study were not appropriate for the typing of non-albicans species (Ergon & Gülay 2005). Some authors highlighted that the strains classified as identical by one primer are not always classified as belonging to the same cluster when analysed by another primer (Bonfim-Mendonça et al 2013).…”
Section: Discussionmentioning
confidence: 91%
“…Coefficients of genetic similarity are indicated in the horizontal line ( S AB ). Vertical line indicates the threshold S AB = 0.81, separating the related and unrelated groupings 20 …”
Section: Resultsmentioning
confidence: 99%
“…Candida species are an important cause of systemic nosocomial infections, being responsible for the major documented fungal infections. 1,20 Epidemiological elucidation of this type of infection and determination of the sources of hospital-acquired C. albicans infections relies mainly on typing methods, which are based on phenotypical or molecular characteristics of the isolates. However, stability of these characteristics after in vitro storage is essential to assure typing methodological validity.…”
Section: Discussionmentioning
confidence: 99%